Genomic and Genetic Insights Into a Cosmopolitan Fungus, Paecilomyces variotii (Eurotiales) - Urquhart, Andrew S.; Mondo, Stephen J.; Mäkelä, Miia R.; Hane, James K.; Wiebenga, Ad; He, Guifen; Mihaltcheva, Sirma; Pangilinan, Jasmyn; Lipzen, Anna; Barry, Kerrie; de Vries, Ronald P.; Grigoriev, Igor V.; et al. (Frontiers in Microbiology, 2018)
Species in the genus Paecilomyces, a member of the fungal order Eurotiales, are ubiquitous in nature and impact a variety of human endeavors. Here, the biology of one common species, Paecilomyces variotii, was explored using genomics and functional genetics. Sequencing the genome of two isolates revealed key genome and gene features in this species. A striking feature of the genome was the two-part nature, featuring large stretches of DNA with normal GC content separated by AT-rich regions, a hallmark of many plant-pathogenic fungal genomes. These AT-rich regions appeared to have been mutated by repeat-induced point (RIP) mutations. We developed methods for genetic transformation of P. variotii, including forward and reverse genetics as well as crossing techniques. Using transformation and crossing, RIP activity was identified, demonstrating for the first time that RIP is an active process within the order Eurotiales. A consequence of RIP is likely reflected by a reduction in numbers of genes within gene families, such as in cell wall degradation, and reflected by growth limitations on P. variotii on diverse carbon sources. Futhermore, using these transformation tools we characterized a conserved protein containing a domain of unknown function (Duf1212) and discovered it is involved in sporulation.